Effect of alcohol on Glasgow Coma score in traumatic brain injury: a single, center, cross-sectional study - Thomas, Minnu; Suseel, Appu; David, Suresh Samuel (International Journal of Research in Medical Sciences, 2023)
Background: To study the effect of blood alcohol levels on GCS in Traumatic brain injury patients (TBI) and relate the findings to brain injury severity based on the admission CT scan. Methods: This cross-sectional study with a comparison group is conducted in Emergency Department (ED) of Pushpagiri Institute of Medical Sciences and Research Centre, Central Travancore, Kerala, India from April 2016 to September 2017 including all patients of 18 - 70 years of age presenting with head injury. 200 participants, 100 each of alcohol intoxicated and non- intoxicated were selected by consecutive sampling. GCS, Blood alcohol concentration-BAC (derived from the reading of alcohol breath analyzer) and admission CT Rotterdam Score are collected and analyzed at the end of study. Results: When CT Rotterdam Score is 1-3, GCS was found to decrease with increase in BAC (Chi-square test p value=0.011; Spearman’s Rank Correlation coefficient rs=-0.326). Independent t –test showed that at BAC 1-100 mg/dl, mean GCS decrease by 1.6 while only same decrease is found when the BAC levels ranges from 100-400 mg/dl. When the CT Rotterdam score is 4-6, no significant correlation was found between GCS and BAC (p value=0.092; rs=0.214). In the presence of alcohol, GCS had sensitivity 87.5% and specificity 70% in comparison to alcohol absent TBI patients (sensitivity 98.5%, specificity 69.7%). When features of hypoxia and shock are present, GCS have good agreement with actual CT findings of TBI. (Kappa coefficient: K 0.659, sensitivity 76%, specificity 100% in alcoholics and K 0.756, sensitivity 100%, specificity 80.6% in nonalcoholic). Conclusions: Even in the setting of alcohol intoxicated TBI patient, Glasgow coma score is a useful tool for quick decision making in emergency department.